2020
DOI: 10.1002/celc.202001490
|View full text |Cite
|
Sign up to set email alerts
|

High Voltage Carbon‐Based Cathodes for Non‐Aqueous Aluminium‐Ion Batteries**

Abstract: Four different forms of carbon: activated carbon (AC) from human hair, AC from hemp fibers, a carbon fullerene extract consisting of C60 and C70 fullerene (CFEx) and Super‐P carbon black were tested and compared as cathodes for non‐aqueous aluminium‐ion batteries (AIBs). These materials differ in their general structure, porosity and morphology. Fullerenes display a crystalline structure, whereas hemp fibers, Super‐P and hair are amorphous in nature. Of all materials, AC obtained from hair recorded the highest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Li-ion 450 55 [40] Cryogenic treated, ZnCl2-activated C. sativa carbon Li-ion 750 74 [30] ZnCl2-activated C. sativa carbon Li-ion 500 74 [28] Ball-milled carbonised C. sativa Li-ion 300 300 [33] Sulfur-doped carbonised C. sativa K-ion 450 200 [30] K-ion full cell 80 50 Carbonised C. sativa doped with red phosphorus nanoparticles K-ion 450 40 [28] Free-standing carbonised C. sativa Na-ion 250 37 [35] N,O-doped carbon nanosheets Na-ion 190 1000 [34] Carbon Valley C. sativa fibres Al-ion 80 50 [42] MnO2 doped, KOH-activated C. sativa carbon Li-S 700 37 [38] *All battery types are in half cell form, unless otherwise stated. Research into C. sativa as an alternative low cost and environmentally benign carbon precursor for supercapacitor applications is worthwhile as most of these devices are primarily based on, or somehow incorporate, activated carbon and carbon black materials in their electrodes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Li-ion 450 55 [40] Cryogenic treated, ZnCl2-activated C. sativa carbon Li-ion 750 74 [30] ZnCl2-activated C. sativa carbon Li-ion 500 74 [28] Ball-milled carbonised C. sativa Li-ion 300 300 [33] Sulfur-doped carbonised C. sativa K-ion 450 200 [30] K-ion full cell 80 50 Carbonised C. sativa doped with red phosphorus nanoparticles K-ion 450 40 [28] Free-standing carbonised C. sativa Na-ion 250 37 [35] N,O-doped carbon nanosheets Na-ion 190 1000 [34] Carbon Valley C. sativa fibres Al-ion 80 50 [42] MnO2 doped, KOH-activated C. sativa carbon Li-S 700 37 [38] *All battery types are in half cell form, unless otherwise stated. Research into C. sativa as an alternative low cost and environmentally benign carbon precursor for supercapacitor applications is worthwhile as most of these devices are primarily based on, or somehow incorporate, activated carbon and carbon black materials in their electrodes.…”
Section: Methodsmentioning
confidence: 99%
“…However, it is worth noting the lack of direct comparison of different biomass precursors within the same system. In fact, of the C. sativa papers reviewed, only one group compared performance against a different biomass: activated human hair against activated C. sativa fibres in a Al-ion battery [42]. They found that the activated human hair electrode exhibited a slightly higher capacity (90 mA h g -1 vs. 80 mA h g -1 , respectively, at a rate of 50 mA g -1 ) and had better rate capability.…”
Section: Sativa Vs Other Biomassmentioning
confidence: 99%
“…The hair activated carbon exhibited great porosity as well as heteroatom presence which ameliorated its performance. Super‐P is incapable of holding charge for prolonged cycles, hemp fiber is unstable whereas fullerene is costly making hair activated carbon among all a suitable cathode material for AIB (Divya & Nann, 2021).…”
Section: Rechargeable Battery Technologiesmentioning
confidence: 99%
“…The hair activated carbon exhibited great porosity as well as heteroatom presence which ameliorated its performance. Super-P is incapable of holding charge for prolonged cycles, hemp fiber is unstable whereas fullerene is costly making hair activated carbon among all a suitable cathode material for AIB (Divya & Nann, 2021). Saroja et al (2020) have developed a disordered carbon nanosheet from biomass (Areca catechu) and embedded it with red phosphorus and used it as a cathode material for AIB (Saroja et al, 2020).…”
Section: Aluminum Ion Batterymentioning
confidence: 99%
“…Any material that can be oxidized could react with the chlorides in the electrolyte and make a nonmetal chloride on charging. In the case of carbon, the C n + 4 n Cl – ⇌ n CCl 4 + 4 n e – reaction has not been demonstrated; carbon oxidation occurs with attachment/intercalation of AlCl 4 – ions instead, C n + AlCl 4 – ⇌ C n [AlCl 4 ] + e − .. Much lower capacities are achieved, generally in the range of 50–200 mAh/g depending on the carbon source. However, there are other materials that could potentially be oxidized to their corresponding chlorides as shown in Figure , via eq . …”
Section: Introductionmentioning
confidence: 99%